Antifungal Activities of Peptides Derived from Domain 5 of High-Molecular-Weight Kininogen. (14th July 2011) - Sonesson, Andreas; Nordahl, Emma Andersson; Malmsten, Martin; Schmidtchen, Artur
Abstract : In both immunocompromised and immunocompetent patients, Candida and Malassezia are causing or triggering clinical manifestations such as cutaneous infections and atopic eczema. The innate immune system provides rapid responses to microbial invaders, without requiring prior stimulation, through a sophisticated system of antimicrobial peptides (AMPs). High molecular weight kininogen (HMWK) and components of the contact system have previously been reported to bind to Candida and other pathogens, leading to activation of the contact system. A cutaneous Candida infection is characterized by an accumulation of neutrophils, leading to an inflammatory response and release of enzymatically active substances. In the present study we demonstrate that antifungal peptide fragments are generated through proteolytic degradation of HMWK. The recombinant domain 5 (rD5) of HMWK, D5-derived peptides, as well as hydrophobically modified D5-derived peptides efficiently killed Candida and Malassezia . Furthermore, the antifungal activity of modified peptides was studied at physiological conditions. Binding of a D5-derived peptide, HKH20 (His 479 -His 498 ), to the fungal cell membrane was visualized by fluorescence microscopy. Our data disclose a novel antifungal activity of D5-derived peptides and also show that proteolytic cleavage of HMWK results in fragments exerting antifungal activity. Of therapeutic interest is that structurally modified peptides show an enhanced antifungal activity.